THE WAYS IN WHICH TEACHERS AND PARENTS WORK MUTUALLY IN THE INCLUSIVE CLASSROOM - Vusala Sardar, Aliyeva (PEARSON JOURNAL, 2020)
In this article, while school-family communication is at the forefront in the inclusive education system, parents are at the other extreme. It is known that children come to school from different families. Therefore, the family is considered to be the first educator. On the other hand, there are many factors that negatively affect student formation in families, and the teacher must be able to determine the nature of these factors, their impact on the parent's personality, and student formation. Although the school and family problems of early childhood, the psychological characteristics of children with disabilities, the individual approach to young students, and theoretically well proven in inclusive education, issues such as how to develop a practical action mechanism, how to overcome the negative effects of the problems remain almost theoretical. The second important factor is the inconsistency in research in this field, which does not give a clear idea about the solution.